Energy poverty leap during the pandemic : the case of Ukraine - Pahlevanzade, Alborz; Goncharuk, Anatoliy; Hromovenko, Kostiantyn; Hrinchenko, Yurii (My University, 2021)
As recent studies showed, the post-communist countries have relatively the highest level of energy poverty in Europe. The poorest of them still are not explored. So, the authors decided to study this problem for Ukraine as one of the largest and poorest post-communist countries in Europe. This Eastern European country experienced a number of challenges before the pandemic, including a war with Russia in the east of the country, high external debt, high energy intensity and low added value of the economy. The purpose of this study is to measure how deep the energy poverty problem in Ukraine is and how it changed during the COVID-19 pandemic. Applying selected quantitative and financial indicators, the authors showed the problem of energy poverty in Ukraine remained acute at the beginning of 2020, especially in terms of heating. Moreover, its level in Ukraine was three times higher than the average level for the all the EU countries. Furthermore, in 2020, duringthe pandemic, there were drastic increasing arrears of households on utility bills that meant a new leap of energy poverty in Ukraine. This study did not search for the causes of the identified leap in energy poverty, which apparently connected with the global and local economic and social consequences of the pandemic. However, it revealed the depth of this problem and the lower impact of the nature factor (air temperature) on energy poverty during and after the COVID-19 pandemic. Further research is required to identify the underlying drivers and develop possible solutions to this problem in Ukraine and other European countries suffering from high energy poverty.
Goncharuk A. Energy poverty leap during the pandemic : the case of Ukraine / A. Pahlevanzade, K. Hromovenko, A. Goncharuk, Y. Hrinchenko // Polityka Energetyczna – Energy Policy Journal. – 2021. – Vol. 24, Issue 2. – P. 5-18.
Keywords: energy poverty; arrears; households; pandemic; Ukraine